2019
DOI: 10.3390/pharmaceutics12010013
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomic Characterization in Bipolar Spectrum Disorders

Abstract: The holistic approach of personalized medicine, merging clinical and molecular characteristics to tailor the diagnostic and therapeutic path to each individual, is steadily spreading in clinical practice. Psychiatric disorders represent one of the most difficult diagnostic challenges, given their frequent mixed nature and intrinsic variability, as in bipolar disorders and depression. Patients misdiagnosed as depressed are often initially prescribed serotonergic antidepressants, a treatment that can exacerbate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 179 publications
0
4
0
Order By: Relevance
“…Although several drugs have been approved for these conditions, their use is often associated with severe side efects or inefcacy. In addition to medical treatment, in recent years, plant-derived products are providing interesting applications both alone in the early phase of the diseases and in association with psychiatric drugs through a network pharmacology approach [58,59]. Herbal medicines, food supplements, and phytotherapy approaches provide a plethora of bioactive molecules and entire phytocomplexes potentially useful for mood disorders [60,61].…”
Section: Depression and Anxietymentioning
confidence: 99%
“…Although several drugs have been approved for these conditions, their use is often associated with severe side efects or inefcacy. In addition to medical treatment, in recent years, plant-derived products are providing interesting applications both alone in the early phase of the diseases and in association with psychiatric drugs through a network pharmacology approach [58,59]. Herbal medicines, food supplements, and phytotherapy approaches provide a plethora of bioactive molecules and entire phytocomplexes potentially useful for mood disorders [60,61].…”
Section: Depression and Anxietymentioning
confidence: 99%
“…Valproate glucuronide is the major VPA metabolite and the reaction of glucuronic acid conjugation is mediated by UGTs, especially UGT1A and UGT2B including UGT1A3 , UGT1A4 , UGT1A8 , UGT1A9 , UGT1A10 , UGT2B15 , and the most prominent UGT1A6 and UGT2B7 . Pharmacogenomic studies have focused on UGT polymorphisms, because genetic UGT variants can influence dosage and plasma drug concentrations and can be directly linked to ADR development [ 75 , 76 ].…”
Section: Genetic Polymorphisms Of Drug Metabolizing Enzymes and Vpmentioning
confidence: 99%
“…Epidemiological statistics showed that the prevalence of BD was about 2% ( Merikangas et al, 2011 ), and the risk of mortality rate due to suicide, which partly attributed to the mood states of BD patients, was 20–30 times higher than that of the normal ( Pompili et al, 2013 ; Orsolini et al, 2016 ; Fornaro et al, 2018 ; De Berardis et al, 2021 ). The early diagnosis of BD is difficult, and the final clinical diagnosis is usually made 5–10 years after the recurrence of the initial symptoms ( Fortinguerra et al, 2019 ). Poor prognosis is another feature of BD, while cognitive dysfunction and poor social regression can be observed in many patients with chronic BD ( Passos et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%